Analysis of the Use of Virgin Coconut Oil as an Alternative Soaking Agent on the Quality of Ctenocephalides felis Preparations - Ayu Daratista; Bagus Muhammad Ihsan; Maulidiyah Salim (MEDICA (International Medical Scientific Journal), 2024)
Preservation preparations are a technique for preserving parasite specimens, including Ctenocephalides felis (cat flea), involving several stages: fixation with 10% KOH, dehydration using graded alcohols (30%, 50%, 70%, 96%, absolute), clearing, and mounting. The clearing process aims to clarify the morphological structure of the parasite. This study aims to investigate the function of virgin coconut oil (VCO) as an alternative to xylene in the clearing stage, in terms of the clarity and quality of the preparation. The research design used is a quasi-experimental approach with purposive sampling technique. The research population consists of fleas, and the sample included 16 cat fleas (Ctenocephalides felis) that underwent the clearing process using virgin coconut oil (VCO). The results of the study showed that out of the 16 preparations, 9 still had residual chitin layers, while 7 did not. Based on the quality of the preparation, there were 7 preparations with good quality (44%), 6 moderately good (38%), and 3 poor (18%). This study concluded that virgin coconut oil is capable of clarifying Ctenocephalides felis preservation preparations and can serve as an alternative to xylene in the clearing process, with the preparation quality being sufficient for microscopic morphological observation of fleas.